COVID-19, poverty and inclusive development. (September 2021) - Gupta, Joyeeta; Bavinck, Maarten; Ros-Tonen, Mirjam; Asubonteng, Kwabena; Bosch, Hilmer; van Ewijk, Edith; Hordijk, Michaela; Van Leynseele, Yves; Lopes Cardozo, Mieke; Miedema, Esther; Pouw, Nicky; Rammelt, Crelis; et al.
Highlights: COVID-19 responses can be assessed using an Inclusive Development and DPSIR framework. COVID-19 responses focus less on Drivers and Pressures, and more on State and Impacts. Global COVID-19 responses implicitly prioritize the privileged. COVID-19 responses are exacerbating the vulnerability of the marginalized, undermining efforts to achieve the Sustainable Development Goals. State funds for COVID-19 recovery should focus on socio-ecological inclusion to reduce risks and vulnerability in the future. Abstract: The COVID-19 epidemic provides yet another reason to prioritize inclusive development. Current response strategies of the global community and countries expose a low level of solidarity with poorer nations and poorer people in all nations. Against this background, this paper addresses the question: What are the development challenges that the COVID-19 pandemic lays bare and what lessons can be learnt for the way recovery processes are designed? Using an inclusive development and DPSIR lens to assess the literature, our study finds that, first, the current response prioritises the 'state' and 'impact' concerns of wealthier classes at the expense of the remainder of the world population. Second, responses have ignored underlying 'drivers' and 'pressures', instead aiming at a quick recovery of the economy. Third, a return to business-as-usual using government funding will lead to a vicious cycle of further ecological degradation, socio-economic inequality and domestic abuse that assist in exacerbating the drivers of the pandemic. We argue instead for an inclusive development approach that leads to a virtuous cycle by emphasizing human health, well-being and ecosystem regeneration. We conclude that the lost years for development did not commence in 2020 with the onset of COVID-19; the downward trend has actually been waxing over the past three decades. From this perspective, COVID-19 may be the shock needed to put the last first and transform vicious into virtuous cycles of inclusive development.